The Sublime Qur'an and Orientalism: By Muhammad Khalifa. Karachi: International Islamic Publishers (Pvt.) Ltd., 1989, 262pp., second edition. (American Journal of Islam and Society, 1991)
The Qur'an, being central to both the Islamic faith and its practice, hasbeen studied in a plethora of orientalist writings-ranging from such a crudelypolemical one as Alexander Ross's English translation of the Qur'an entitledThe Alcoran of Mahomet . . . for the Satisfaction for all those who Desireto look into the Turkish Vanities (1649) to those with scholarly pretensionsand claiming to be "objective" studies, such as Noldeke's Geschichte des Qorans(1860), Goldziher's Die Richtungen der islamischen Koranauslesung (1920),Bell's The Quran translated with a Critical Rearrangement of the Surahs(1937-39), Wansbrough's Quranic Studies (1977), and Burton's The Collectionof the Quran (1977).The book under review, first published in 1983, recounts the full tockof the orientalists' misconceptions, down the ages, about the Qur'an-theiroutlandish theories about its authorship (pp. 7-18), their assaults on its textualhistory and its arrangement (pp. 52-63), their brazen attempts at twistingits meaning in their Qur'an translations (pp. 64-92), and their bizzare viewson abrogation in the Qur'an (pp. 93-104). Khalifa deserves every credit forassembling so much information. What is more remarkable is that it is followedby a stout refutation of these allegations about the form and contents of theQur'an and an extensive, authentic exposition of the Qur'anic teachings,concepts, and morals, all of which constitutes the second part of the book(pp. 111-205). In elucidating the Qur'anic worldview, Khalifa's discussion issubtle, in large part persuasive, tenaciously pursued, and well presented.Appended to the book are two highly informative appendices on the orderof the Qur'an's surahs.This well-intentioned and detailed scholarly study, however, does notreally succeed in delivering what its title promises. In discussing the orientalists'ventures into establishing the chronology of Qur'anic surahs, Khalifa sayslittle about Gustav Fli:lgel's Corani Textus Arabiscus (1834) and the theoriespropounded by Grimme and Hirschfield's New Researches in the Compositionand Exegesis of the Quran (1902). More serious is the lack of any referenceto a host of orientalists' writings on the philological and lexical aspects ofthe Qur'an, namely Baljon's Modern Muslim Quran Interpretation (1961),Torrey's The Commercial-Theological Terms in the Quran (1892), Watt's ...